State-Dependent Memory: Neurobiological Advances and Prospects for Translation to Dissociative Amnesia - Radulovic, Jelena; Lee, Royce; Ortony, Andrew (Frontiers in Behavioral Neuroscience, 2018)
In susceptible individuals, overwhelming traumatic stress often results in severe psychopathologies such as post-traumatic stress disorder (PTSD) or dissociative disorders. Among other symptoms, these disorders are defined by severe abnormalities of memory processing, manifested either as the uncontrollable emergence of memories (flashbacks) or as an inability to remember events (dissociative amnesia) that are usually, but not necessarily, related to the stressful experience. These memory deficits are believed to be the core source of debilitating psychopathologies such as anxiety, depression, and social dysfunction. The question of why memory for some traumatic experiences is compromised while other comparably traumatic experiences are remembered perfectly well, both within and across individuals, has puzzled clinicians for decades. Whereas much effort has been invested in gaining a better understanding of memory processing in PTSD, the mechanisms underlying memory deficits in dissociative disorders have remained elusive. In this article, we present clinical, cognitive, and neurobiological perspectives on memory research relevant to dissociative amnesia. Given that state-dependence has been a widely accepted conceptual frameworks of memory processing in dissociative amnesia, we focus on this phenomenon by discussing its basic features in humans and proposing how advances in the neurobiology of state-dependent memory gleaned from animal studies could be translated to humans.